2016
DOI: 10.1093/femspd/ftw079
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and oral vaccination improves protection conferred by the live vaccine strain against pneumonic tularemia in the rabbit model

Abstract: Tularemia is a severe, zoonotic disease caused by a gram-negative bacterium, Francisella tularensis We have previously shown that rabbits are a good model of human pneumonic tularemia when exposed to aerosols containing a virulent, type A strain, SCHU S4. We further demonstrated that the live vaccine strain (LVS), an attenuated type B strain, extended time to death when given by scarification. Oral or aerosol vaccination has been previously shown in humans to offer superior protection to parenteral vaccination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…These data suggest that BHI-grown SCHU S4 is a more rigorous challenge for demonstrating protection in vaccine studies than MHB-grown SCHU S4. Considering that we have previously shown that attenuated derivatives of SCHU S4 outperform LVS and protect rabbits well against both morbidity and mortality at even higher challenge doses of SCHU S4 grown in BHI, this further illustrates the superior performance of these attenuated derivatives as potential vaccine candidates (4)(5)(6). Both the survival of LVS-vaccinated rabbits and the consistent/higher SF from the aerosol characterization studies argue that BHI-grown F. tularensis should be used in pivotal F. tularensis efficacy studies to achieve a rigorous, reproducible aerosol challenge sufficient to demonstrate the efficacy of potential vaccine candidates in animals.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…These data suggest that BHI-grown SCHU S4 is a more rigorous challenge for demonstrating protection in vaccine studies than MHB-grown SCHU S4. Considering that we have previously shown that attenuated derivatives of SCHU S4 outperform LVS and protect rabbits well against both morbidity and mortality at even higher challenge doses of SCHU S4 grown in BHI, this further illustrates the superior performance of these attenuated derivatives as potential vaccine candidates (4)(5)(6). Both the survival of LVS-vaccinated rabbits and the consistent/higher SF from the aerosol characterization studies argue that BHI-grown F. tularensis should be used in pivotal F. tularensis efficacy studies to achieve a rigorous, reproducible aerosol challenge sufficient to demonstrate the efficacy of potential vaccine candidates in animals.…”
Section: Discussionmentioning
confidence: 52%
“…One argument against using the rabbit for tularemia vaccine studies had been that vaccination with LVS extended the time to death but not survival (5,6,10,21). Our own prior studies are included in those findings, including the observation that oral inoculation or inhalation of LVS did extend the rabbit time to death more than subcutaneous inoculation, with one oral LVS-vaccinated rabbit surviving challenge (5). These data do fit with what has been reported in humans and monkeys, where oral and aerosol LVS vaccination offered better protection against subsequent respiratory challenge (17,20,34,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One argument against using the rabbit for tularemia vaccine studies had been that vaccination with LVS extended time to death but not survival (5, 6, 10, 21). Our own prior studies are included in those findings, including the observation that oral inoculation or inhalation of LVS did extend rabbit time to death more than subcutaneous inoculation (5).…”
Section: Discussionmentioning
confidence: 99%
“…One argument against using the rabbit for tularemia vaccine studies had been that vaccination with LVS extended time to death but not survival (5, 6, 10, 21). Our own prior studies are included in those findings, including the observation that oral inoculation or inhalation of LVS did extend rabbit time to death more than subcutaneous inoculation (5). This data does fit with what has been reported in humans and monkeys where oral and aerosol LVS vaccination offered better protection against subsequent respiratory challenge (17, 20, 35, 36).…”
Section: Discussionmentioning
confidence: 99%